Good governance at district level: A case study of district planning - Sharma, Rajesh (1998)
Examining empirically the district plan implementation process in a Bihar district as a mode of judging operationalising of good governance at the local level on the basis of indices related thereto, the author discusses various problems noticed in this regard in his study pertaining to: processes involved in selection, approval, allocation, etc., of schemes. While identifying causes thereof, he also suggests possible solutions in the light of findings of his study. - Reproduced
Keywords: Good governance - India - Bihar; Public administration - India - Bihar; District planning - India - Bihar; Good governance